Beyond Understanding of Student Attitudes Towards 'Grammar Naziness' in Facebook Discourse - Basis for Grammar Teaching - Anthony Alimonsurin; Blossom B. Gasper (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Facebook is one of the most widely used social media applications of the learners of todays’ generation. However, the respondents showed reluctance in engaging in discussions about English grammar in the Facebook comment section, indicating a preference for private correction rather than public discourse. Additionally, the study revealed that non-native speakers of English perceived making grammar mistakes on Facebook as a valuable learning experience. Based on these findings, it can be concluded that students are receptive to corrective feedback but prefer a more discreet approach to grammar teaching on Facebook. The study also highlights the potential of Facebook as a platform for teaching English grammar, emphasizing the importance of positive reinforcement and sensitivity when providing feedback. To optimize the use of Facebook for grammar teaching, the researchers recommend careful planning to ensure students do not feel ashamed or demotivated when posting their statuses. It is crucial to incorporate positive reinforcement and consider the sensitivity of students when providing insights on teaching grammar in the Facebook context. Furthermore, it is advised to conduct a thorough investigation into the openness of respondents to accept corrective feedback on Facebook and provide an orientation to the subjects regarding the observation of their Facebook posts. Overall, this study provides valuable insights into student attitudes towards 'Grammar Naziness' on Facebook and offers practical recommendations for effective grammar teaching in an online discourse setting.